Wykorzystanie gier komputerowych z czujnikiem ruchu typu Kinect w ćwiczeniach korygujących wady postawy - Prusińska, Violetta; Strugarek, Jan; Wieczorek, Jakub (Studia Edukacyjne, 2021)
The development of science and technology brings about many advantages for human beings, yet it also creates a risk for their health and correct growth, including problems with right posture among children. The fast pace of life, an increasing number of tasks in- and outside of school, lack of physical activity, bad dietary habits and permanent compression of vertebrae are the main factors responsible for posture problems among child and teenager groups. The ages between 7 and 10 seem to be a critical period for forming the body position and it is connected with changing children’s daily learning routine (from free and loose activity to a few-hour sitting position at school). In effect, about 60% of children suffer from postural problems. This percentage has a rising tendency as such problems increase with age. The prevention and treatment of consequent disorders is based e.g. on physical exercise during corrective gymnastic classes, where a number of new technology solutions to improve standard and quality of such classes are used, e.g. motion sensors (Microsoft Kinect). This article connects corrective exercises with motion-control-based computer games. This approach uses the natural interest of children for interactive games to improve their engagement in corrective exercises. This new form of health-related activity packed in a “computer driven case” is a real chance to make corrective exercises more children-friendly and thus to stimulate children’s motivation to actively participate in them.